Dampak Perceraian Orang Tua Terhadap Perilaku Beragama Remaja Di Desa Klambir V Kebun Kabupaten Deli Serdang - Amanda, Gilang Surya; Muktarruddin, Muktarruddin (Kamaya: Jurnal Ilmu Agama, 2024)
Divorce is the breaking of marital ties between husband and wife both religiously and by court. This divorce has an impact on children both social, psychological and religious impacts. This study aims to determine and reveal the impact of parental divorce on the religious behavior of adolescents in Klambir V Village, Hamparan Perak District, Deli Serdang Regency. The method uses descriptive qualitative methods through a field / case study approach consisting of five informants using data collection techniques, observation, interviews and documentation by analyzing miles and huberman and using data validity in the form of triangulation.  The results are that religious behavior due to divorce in adolescents in Klambir Village is low and has a very negative impact, there are factors of divorce in Klambir V Kebun Village, Hamparan Perak District, Deli Serdang Regency, namely: economy, infidelity, night out, lack of attention and affection, lack of sense of responsibility and incompatibility between the two partners both in terms of views, vision-mission of marriage and personal between themselves.  The impact of religious behavior is opening the aurat, being lazy to pray, leaving prayers, neglecting and violating religious rules by dating, getting drunk, promiscuity and free sex, fighting parents by saying harsh words and ignoring the words of parents. Conclusion Parental divorce has a negative impact on adolescent religious behavior.